Le judaïsme à Montréal - Robinson, Ira (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs

Les rapports entre les francophones et Juifs dans le contexte montréalais - Anctil, Pierre (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Francophones; Juifs

L’intégration socio-scolaire et les stratégies identitaires d’adolescents iraniens à Montréal - Aghasi-Sorkhabi, Lida (Université de Montréal, 2010)
Keywords: Iraniens

Les trajectoires de l'intégration professionnelle des immigrants iraniens travaillant comme chauffeurs de taxi à Montréal - Namazi, Vahideddin (Université de Montréal, 2010)
Keywords: Iraniens

Les maux de ventre des enfants haïtiens de Montréal: entre la recomposition culturelle et la souffrance familiale - Gomez Cardona, Liliana (Université de Montréal, 2010)
Keywords: Enfants; Haïtiens

L’impact du loisir sur l’intégration sociale des minorités ethniques à Montréal: le cas des nouveaux arrivants originaires du Pérou - Murrugarra Cerna, Juan Carlos (Université de Montréal, 2010)
Keywords: Péruviens

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989). La création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordán González, Laura Francisca (Université de Montréal, 2010)
Keywords: Chiliens; Musique

Migrations juives marocaines au Canada ou comment devient-on sépharade? - Cohen, Yolande (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs; Maghrébins; Marocains

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Number: 2
Keywords: Femmes; Travail

Invisible Migrants: The Case of Russians in Montreal - Gingras, Phillip (Université Concordia, 2010)
Keywords: Russes

Where Do I Belong? Narratives from the Lives of Iranians in Montreal - Dehghani Estarki, Mahdi (Université McGill, 2010)
Keywords: Iraniens

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

"We Started Over Again, We Were Young": Postwar Social Worlds of Child Holocaust Survivors in Montreal - Sheftel, Anna; Zembrycki, Stacey (Urban History Review / Revue d'histoire urbaine, 2010)
issued: 2010-23-00
Keywords: Clubs; Enfants; Juifs

L'accès au logement par les nouveaux arrivants à Montréal: le cas des réfugiés et demandeurs d'asile en provenance d'Afrique subsaharienne - Charette, Alexandra (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2010)
Keywords: Africains; Logement

Lorsque l'imaginaire migratoire rencontre les réalités de la migration: parcours de migrants volontaires et qualifiés de l'Afrique de l'Ouest au Québec - Michaud, Valérie (Université de Montréal, 2010)
Keywords: Africains

Au cœur des institutions d'immigration: dispositifs, gestion et contrôle migratoire au Canada - Haince, Marie-Claude (Université de Montréal, 2010)

Vieillir ailleurs: options identitaires et paroles d'aînés d'origine libanaise - El-Hage, Habib (Université du Québec à Montréal, 2010)
Keywords: Libanais